CONTENT ANALYSIS OF VALUE OF CHARACTER: A CASE STUDY OF PHYSICS TEXTBOOK IN REMBANG REGENCY - Fitriyah, Maghfirotul; Made D.P, Ngurah; Yulianto, Agus (Unnes Science Education Journal, 2017)
Textbooks play an important role in learning. One of its functions is to implement the value of character education. It is therefore important to analyze the content of the character values in a textbook. This research aims at revealing: (1) the characteristics of the character value content in physics textbooks of the 2013 curriculum at eleventh grade and conformity to map the value for high school students based material development of the nation's culture and character education, (2) the suitability approach to character education in textbooks within the framework of the comprehensive approach, as well as (3) the display characteristics of integration character values in the textbook. The research method is inferential content analysis with the quantitative-qualitative descriptive approach. The subjects were two eleventh grade physics textbooks on dynamic fluid material that refers to the 2013 curriculum and those widely used as the primary learning resources in the district of Rembang.The content analysis of character values involved three independent raters who were given the structured observation sheets. Book A contains 15 of 18 values with the most dominant responsibility of 14.81%. While book B contains 12 values and dominated by the value of curiosity of 16.67%. Both of the books have not fully implemented a comprehensive approach. The presentation of the value of characters in both books is integrated implicitly and explicitly.